Aplikasi My Angkot - Sofyan Mufti Prasetiyo; Mahardika Paramarta Laia; Dewy Suciati; Nurul Syifa Fauzia Paksi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Public transportation is a means of transportation for the community to facilitate transportation in everyday life. Public transportation is the main choice because everyone can use it and the fare is relatively cheap to get to their destination. Most people use this facility to travel or to get to their destination. The need to know the fastest angkot route is quite urgent for angkot service users, especially those who are inexperienced. So, it is necessary to have an application regarding public transport routes and can avoid jostling with other passengers. Then the "My Angkot" application was designed. which can make it easier for users of public transportation services to access information on public transportation for the city of South Tangerang easily and practically. In this study using the Waterfall method and software has been created to solve the problem of finding public transport routes and to avoid being jostled with other passengers in order to facilitate public transportation services for both natives and immigrants. The My Angkot application is expected to make it easier for users to get information about public transportation in the city of South Tangerang and can generate the shortest path and other routes.